Sistem Informasi Persediaan pada PT. XYZ Berbasis Desktop - Tri Pratiwi Olivia Riska Bokings; Cindy Julia Putri (Masyarakat Ekonomi Syariah Bogor, 2024)
The Inventory Information System is a key element in enhancing the operational efficiency of companies, particularly in the manufacturing industry. This research aims to analyze, design, and implement an inventory information system for PT. XYZ to address challenges in raw material inventory management, especially the manual return system. The research methodology includes data collection techniques such as interviews, observations, and literature review. Primary data were obtained through direct interviews with relevant parties at PT. XYZ and on-site observations. Data analysis employed the PIECES method (Performance, Information, Economic, Control, Efficiency, Service) to evaluate the weaknesses of the existing system and formulate improvement proposals. The system development utilized the SDLC Waterfall method, encompassing requirement analysis, design, coding, testing, and implementation. The stages included analyzing the current system, designing the inventory information system, developing a program based on the design, testing the system using Blackbox and User Acceptance Testing (UAT), and implementing the new system in PT. XYZ's production environment. The testing results, including UAT, demonstrated that the inventory information system successfully produced the required outputs, with an overall test result percentage of 84%, indicating the system's high quality.